EFFECT OF ADDITION OF COCONUT WATER AS ENRICHMENT OF Spirulina platensis GROWTH MEDIA IN LABORATORY SCALE - Khasena, Aisyah; Nurrachmi, Irvina; Zulkifli, Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Spirulina platensis is a microalga that has high economic value. The growth of S.platensis is influenced by environmental conditions and nutrients. The objectives of this study are to determine the best concentration of coconut water for media of S.platensis growth. The study was conducted at the Natural Feed Laboratory of the Brackish Water Aquaculture Center (BPBAP) Ujung Batee Aceh. This research is an experimental study using a completely randomized design (CRD) consisting of 3 levels of treatment and control using coconut water of the media with concentrations of 3%, 5%, and 7% with 3 replications. The highest cell density level of S.platensis reached 83.102 cells/ml in treatment A (3%), in treatment B (5%) 73.975 cells/ml, the density in the control treatment reached 70.850 cells/ml, and in treatment, C (7%) cell density only reached 54.658 cells/ml. The results of the ANOVA test on day 2, day 3, day 5, and day 6 showed that the addition of coconut water with different concentrations had a significant effect (p<0.05) on the growth of S.platensis.